Writing and Rewriting Abd El-Krim El-Khattabi’s Memory (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Mohammed Ben Abd el-Krim el-Khattabi (1882 – 1963) is a prominent and controversial figure in Moroccan history. His memory continues to draw interest among Moroccan citizens, as shown by the display of his images during the Ḥirāk demonstrations in 2017. Considering the ongoing influence of Abd el-Krim’s memory on Moroccan society, the Maḫzan has used several official channels, such as the educational system, to shape the narrative around his legacy. An analysis of Moroccan high school history textbooks and interviews with history teachers suggests that Abd el-Krim is widely recognized as an anti-colonialist and Moroccan nationalist. However, some interviews with high school teachers also reveal that contentious representations of this figure exist in the Moroccan educational system. Consequently, as long as Moroccan citizens persistently promote contrasting interpretations of this story, speaking about Abd el-Krim will remain sensitive and controversial.
Keywords: Abd el-Krim el-Khattabi; Contrasting representations; Ḥirāk; Moroccan educational system